2010
DOI: 10.1007/s00104-010-1922-6
|View full text |Cite
|
Sign up to set email alerts
|

Transorale partielle Parathyreoidektomie

Abstract: Improvements in minimally invasive surgical techniques have resulted in the development of natural orifice transluminal endoscopic surgery (NOTES) to minimize operative trauma and perioperative morbidity. Considering the embryologic origin and development of the thyroid and parathyroid glands and their descent during embryogenesis into the final position in the neck, a transoral access to the thyroid region via a sublingual mucosal incision seems to be feasible. After implementation and improvement of a transo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For example, Fowkes et al [7] reported the feasibility of evaluating and diagnosing pleural disease using a single cervical incision in 15 patients. Karakas et al [8] reported the safety of the transoral method for partial parathyroidectomy in a 37-year-old woman with primary hyperparathyroidism. More recently, Wilhelm et al [9] reported the safety and feasibility of the transoral approach for the performance of thymectomy in a live pig.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Fowkes et al [7] reported the feasibility of evaluating and diagnosing pleural disease using a single cervical incision in 15 patients. Karakas et al [8] reported the safety of the transoral method for partial parathyroidectomy in a 37-year-old woman with primary hyperparathyroidism. More recently, Wilhelm et al [9] reported the safety and feasibility of the transoral approach for the performance of thymectomy in a live pig.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to others [5], we were able to gain significant results concerning microbiologic examinations of the operation field or possible injuries of the recurrent laryngeal nerves at risk. We also performed additional hemithyroidectomies and parathyroidectomies in human cadavers [6].Based on the results of these experiments, we were able to establish the new transoral approach in the clinical setting and recently performed a transoral partial parathyroidectomy on two female patients with primary hyperparathyroidism [7]. In conclusion, it is correct to state that our study was the first to demonstrate the feasibility of a transoral resection of parathyroid glands and thyroid lobes using an entirely transoral access to the thyroid region.…”
mentioning
confidence: 73%
“…Based on the results of these experiments, we were able to establish the new transoral approach in the clinical setting and recently performed a transoral partial parathyroidectomy on two female patients with primary hyperparathyroidism [7]. In conclusion, it is correct to state that our study was the first to demonstrate the feasibility of a transoral resection of parathyroid glands and thyroid lobes using an entirely transoral access to the thyroid region.…”
mentioning
confidence: 77%
“…2). A small series of transoral parathyroidectomies for primary hyperparathyroidism has been reported [56,58], while recent investigations have utilized surgical robotics for thyroid resection and neck dissection in human cadavers [59]. …”
Section: Transoral Proceduresmentioning
confidence: 99%
“…After implementation and improvement of this transoral access to the thyroid region in an animal model and in human cadavers [55,56,57,58], the NOTES concept has been applied to the surgery of the thyroid and parathyroid glands (fig. 2).…”
Section: Transoral Proceduresmentioning
confidence: 99%